Net effect of wealth on health for COVID-19 – worldwide state comparison - Żółtaszek, Agata; Olejnik, Alicja (Rozwój Regionalny i Polityka Regionalna, 2024)
The wealth-health relationship is not unambiguous and constant. Indeed, a higher level of wealth affects individual and population health in two opposite ways. Increased risk factors raise the probability of some diseases. Conversely, better healthcare and awareness reduce the chances of developing these diseases or raise the likelihood of treatment and cure. Therefore, the overall impact on health or the “net effect” of wealth (positive or negative) may be challenging to determine. Moreover, this effect may not be fixed for different income groups. Thus, it states to reason that there may exist an “affluence point” changing the predominant impact of wealth (positive/negative), which we will refer to as the “health economic threshold”. This paper aims to assess and quantify the hard-to-grasp overall impact of prosperity on the prevalence and mortality of COVID-19. In particular, we attempt to estimate both the net effect of affluence and the health economic threshold by applying a dedicated analytical tool and problem-specific forecasting methods. Namely, we employ the existing idea of joinpoint regression to produce a specification that models the relationship between GDP and prevalence or mortality which is allowed to exhibit non-constant monotonicity. Finally, we calculate the numerical value of the net effect of affluence through extrapolation. Our results show that for COVID-19 morbidity and mortality, up to a certain level of GDP, the richer the country, the higher the prevalence. After exceeding this threshold, the number of cases stabilises at a very high level, while mortality decreases along with the prosperity of countries. It turned out that the countries of Western and Northern Europe used their wealth effectively, significantly reducing mortality. Unfortunately, in CEE the net effect of wealth was insignificant. Therefore, even with relatively high levels of prosperity compared to the rest of the world, governments and health systems have not risen to the challenge.